Pengaruh Suhu Makanan Terhadap Daya Terima Makanan Di Rumah Sakit - Akila Lalita Widi; AASP Chandra Dewi; Reni Sofiyatin; Luh Suranadi (Poltekkes Kemenkes Mataram, 2020)
Background : Food acceptance is one of indication that could be evaluate for the hospital service especially from aspect of food dishes. The factors who needed attention is food temperature which one of food dishes not warm enough has opportunity to waste 3,8 times be compared by warm food. Methods : This is study literature that obtained from 4 databases among them the national library E-resources, portal garuda, pubmed, and google scholar with using inclusion criteria. Key words used in this literature search include: “food temperature”, “time accurancy”, “the acceptability of food”, “food waste”, “plate waste”. Results : By journals who has review, 3 of them stated that there are effect of food temperature to food acceptance, and one of them stated there aren’t effect of food temperature to food acceptance because another factors videlicet internal nor external factors. The range of best food dishes temperature from lunch time 35°C-44,9°C and soup’s menu evenly served at <60°C.